Structural and functional characterization of the IgSF21-neurexin2α complex and its related signaling pathways in the regulation of inhibitory synapse organization - Chofflet, Nicolas; Naito, Yusuke; Pastore, Anthony John; Padmanabhan, Nirmala; Nguyen, Phuong Trang; Poitras, Christian; Feller, Benjamin; Yi, Nayoung; Van Prooijen, Jeremie; Khaled, Husam; Coulombe, Benoit; Clapcote, Steven J.; et al. (Frontiers in Molecular Neuroscience, 2024)
The prevailing model behind synapse development and specificity is that a multitude of adhesion molecules engage in transsynaptic interactions to induce pre- and postsynaptic assembly. How these extracellular interactions translate into intracellular signal transduction for synaptic assembly remains unclear. Here, we focus on a synapse organizing complex formed by immunoglobulin superfamily member 21 (IgSF21) and neurexin2α (Nrxn2α) that regulates GABAergic synapse development in the mouse brain. We reveal that the interaction between presynaptic Nrxn2α and postsynaptic IgSF21 is a high-affinity receptor-ligand interaction and identify a binding interface in the IgSF21-Nrxn2α complex. Despite being expressed in both dendritic and somatic regions, IgSF21 preferentially regulates dendritic GABAergic presynaptic differentiation whereas another canonical Nrxn ligand, neuroligin2 (Nlgn2), primarily regulates perisomatic presynaptic differentiation. To explore mechanisms that could underlie this compartment specificity, we targeted multiple signaling pathways pharmacologically while monitoring the synaptogenic activity of IgSF21 and Nlgn2. Interestingly, both IgSF21 and Nlgn2 require c-jun N-terminal kinase (JNK)-mediated signaling, whereas Nlgn2, but not IgSF21, additionally requires CaMKII and Src kinase activity. JNK inhibition diminished de novo presynaptic differentiation without affecting the maintenance of formed synapses. We further found that Nrxn2α knockout brains exhibit altered synaptic JNK activity in a sex-specific fashion, suggesting functional linkage between Nrxns and JNK. Thus, our study elucidates the structural and functional relationship of IgSF21 with Nrxn2α and distinct signaling pathways for IgSF21-Nrxn2α and Nlgn2-Nrxn synaptic organizing complexes in vitro. We therefore propose a revised hypothesis that Nrxns act as molecular hubs to specify synaptic properties not only through their multiple extracellular ligands but also through distinct intracellular signaling pathways of these ligands.